Numerical analysis of strain and stress state in cylindrical notched tensile specimens - Derpenski, L.; Seweryn, A. (Фізико-хімічна механіка матеріалів, 2013)
The paper presents the numerical results of stress and strain distribution in specimens with various sizes of notches in monotonic uniaxial tensile tests. The adopted method involves the finite element method and the elastic-plastic model of material with hardening. The distribution of the principal strain, principal stress and maximum plastic shear strain in the plane of notch symmetry is shown in figures.